Governing European Energy Commons: Rules and Local Conditions in Spain - Atutxa Ordeñana, Ekhi; Zubero Beascoechea, Imanol; Calvo-Sotomayor, Iñigo (Convergencia Revista de Ciencias Sociales, 2024)
This paper analyzes Local Energy Communities within the paradigm of the commons and explores their key aspects of collective governance. Utilizing 18 in-depth semi-structured interviews with Spanish Energy Communities, this study examines their internal dynamics and their context interactions. The findings contribute to the understanding of Energy Communities, informing the development of more effective policies. The study reveals the adoption of diverse legal forms by Energy Communities, characterized by decentralized and democratic structures aimed at facilitating a fair energy transition. Moreover, they incorporate social inclusion mechanisms to mitigate economic exclusion. Finally, the commitment of these communities to reshaping the energy model is underscored, which involves defining both the material and spatial boundaries of production and consumption.